Is CO2 gas unsufflator necessary for laparoscopic training in animals? - Tiraboshi,Ricardo Brianezi (2003)
OBJECTIVE: To verify the efficacy and safety of compressed air to produce pneumoperitoneum for laparoscopic surgery in pigs for a training program of residence. METHODS: Dalland pigs weighing 15-17kg underwent general anethesia and mechanical ventilation. They were divided in 3 groups: A - (38) the pneumoperitnoneum was established with an automatic CO2 insufflator, B - (7) as in A except the CO2 gas was changed by compressed air, and C - (11) abdomen insufflation was obtained with compressed air directly from hospital pipe network system. Intra-abdominal pressure in all groups was kept between 12 and 15 mmHg. The laparoscopic procedures performed were distributed proportionally among groups: 20 bilateral nephrectomy, 20 dismembered pyeloplasty and 16 partial nephrectomy. Arterial blood sampling for gasometry was obtained before and 2h after establishment of pneumoperitoneum in 5 pigs of group C. RESULTS: The cost of 25 4,5kg CO2 container used in group A was R$ 3,150.00 (U$ 1,050.00). The mean length time of surgeries in groups A, B and C were respectively: 181±30min, 196±39min e 210±47min (p>0.05). Respiratory alkalosis occurred in 3 out of 5 pigs of group C. No animal exhibited signs of gas embolism or died during surgery. CONCLUSION: The use of compressed air for laparoscopy in pigs was safe, reduced costs and did not require the use of an automatic gas insufflator.